Quitosana ativada com divinilssulfona como um novo suporte para imobilizar e estabilizar enzimas - Pinheiro, Bruna Bandeira (2017)
A new heterofunctional support, chitosan-divinylsulfone, is proposed in this study. The use of chitosan as a support for immobilization of enzymes is very promising since it has characteristics that make it ideal for this function as good mechanical and chemical resistance besides be a biodegradable polymer, renewable and low cost. The divinylsulfone (DVS) has been chosen as an activated agent because can interact with hydroxyl and amino groups of chitosan, in addition can interact with different groups of enzymes, such as: amino, phenol, imidazole or thiol. The support were prepared introducing 7.5 mL of divinylsulfone (DVS) at 10g of chitosan at three differents pHs (10, 12.5 and 14) of sodium carbonate buffer. The enzyme choosed was Lipase B from Candida antarctica (CALB) because has high stability and enantioselectivity being able to act in various reactions of industrial interest. In this context, the study of activation support chitosan with divinylsulfone (DVS) was conducted in order to immobilize CALB. The best results of immobilization were at pH 12.5 of activation conditions of chitosan with divinylsulfone (DVS). Under these conditions, it was obtained 2.87 ± 0.06 U/g of derivative activity, 79.37 % of immobilization yield and almost 50 % of recovery activity. However, the bests results for inactivating thermical was for immobilized enzymes on chitosan activated at pH 10, where the best results did not reach the half-life after 24 and 48 hours, been more than 480 times and 960 times more stable than the free enzyme, respectively. Finally some derivatives were applied in model reaction of hydrolysis reaction of the ethyl hexanoate at pH 5, 7 and 9.2 getting the best activity at pH 5. The results show that the support activated with divinylsulfone is very promising and improved the enzyme stability.